2015
DOI: 10.3109/09273972.2014.1002621
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining Density of Suppression Measurement in Strabismus

Abstract: Test-retest reliability issues may be present for the two filter bars currently still under manufacture. Changes in testing conditions do not significantly affect test results, provided the same filter bar is used consistently for testing. Further studies in children with strabismus having active amblyopia treatment would be of benefit. Despite extensive use of these tests in the UK, this is to our knowledge the first study evaluating filter bar equivalence/reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…This test was difficult to administer (only seven of the children approached were able to perform it). Given the small sample size, and reports of poor test-retest reliability of this test, 50 we do not consider these data further.…”
Section: Orthoptic Assessmentmentioning
confidence: 99%
“…This test was difficult to administer (only seven of the children approached were able to perform it). Given the small sample size, and reports of poor test-retest reliability of this test, 50 we do not consider these data further.…”
Section: Orthoptic Assessmentmentioning
confidence: 99%
“…Other studies have similarly reported limited test-retest reliability of the Flashlight W4D with NDF method. 12 Potentially the improved success rate and reliability with W4DApp is due to the continuous nature of the measures, which allow the contrast to be dropped in small numerical increments, whereas the Flashlight W4D is limited by the ordinal measures of the filter bar, with only 6 density intervals available. 10,11 Despite favorable success rate and reliability, the W4DApp measures of suppression depth were found to have no absolute agreement or significant correlation with the current clinical Flashlight W4D + NDF or the laboratory-based CBI techniques.…”
Section: Discussionmentioning
confidence: 99%
“…2 A 6-filter neutral density (NDF) bar (0.3-log-unit increments, range 0.3d-1.8d) 10 was used in combination with the flashlight to vary light intensity of the stimulus viewed by the dominant eye. 12 The relationship between NDF filter and light intensity was determined from 3 averaged luminance colorimeter readings of the light source through the range of filters.…”
Section: Flashlight W4dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find robust changes of interocular suppression in our anisometropic amblyopes (8/10). Since both studies contain a small number of subjects, whether this is due to the individual variability or a poor test-retest reliability of the quantitative clinical test, even in adults (Piano and Newsham, 2015), remains to be resolved. Furthermore, a luminance-based interocular suppression test (i.e., the Sbisa bar test) in the study of Kehrein et al (2016) and a more quantitative laboratory, contrastbased interocular suppression test (i.e., the binocular phase combination task) in the current study might reflect different mechanisms that underlie interocular suppression .…”
Section: Discussionmentioning
confidence: 99%